13. CLINICAL AND PARACLINICAL CHARACTERISTICS AND STUDY SOME RISK FACTORS FOR DRUG RESISTANCE IN THE TREATMENT OF DRUG-RESISTANT EPILEPSY IN CHILDREN AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objectives: Describe clinical and paraclinical characteristics and study some risk factors for drug resistance in the treatment of drug-resistant epilepsy in children.Subjects and methods: Cross-sectional descriptive study on 96 children with epilepsy treated as outpatients and inpatients at the Department of Neurology, Nghe An Obstetrics and Pediatrics Hospital from January 2024 to October 2024, divided into 2 groups: drug-resistant epilepsy (n = 41) and drug-responsive (n = 55). Patients were diagnosed with drug-resistant epilepsy and drug-responsive according to the International League Against Epilepsy (ILAE 2010) criteria.Results: 96 children with epilepsy included 47 females (49%) and 49 males (51%). Drug-resistant epilepsy in the group of children with a history of status epilepticus accounted for 31.7%, a history of neonatal seizures accounted for 43.9%, a history of febrile seizures accounted for 56.1%, and a history of delayed psychomotor milestones accounted for 92.7%. The average age of onset in the drug-resistant epilepsy group was 10.66 ± 13.0 months, and the average seizure frequency in the drug-resistant epilepsy group per day was 12.12 ± 8.4. The results of paraclinical analysis of EEG and abnormal brain MRI in the drug-resistant epilepsy group accounted for 85.4% and 48.8%, respectively. Multivariate regression analysis showed that a history of neonatal seizures, a history of febrile seizures, status epilepticus, delayed psychomotor milestones, abnormal EEG and MRI were factors related to drug-resistant epilepsy.Conclusion: The medical history, clinical and paraclinical characteristics in epilepsy including history of neonatal seizures, history of febrile seizures, status epilepticus, delayed psychomotor development, abnormal EEG and MRI are factors related to drug-resistant epilepsy
Keywords: Childhood; epilepsy; drug-resistant epilepsy